Molten salts chemistry from lab to applications - Lantelme, Frederic; Groult, Henri (Elsevier, 2013)
"In recent years, molecular modelling has become an indispensable tool for studying the structure and dynamics of molten salts. In this chapter we first provide a short description of the state-of-the-art models and methods used for modelling molten salts at the atomic scale. In particular, we discuss the importance of polarization effects for obtaining accurate results. We then give some examples of the structure of several molten salts, as yielded by the simulations. We finish by describing how the transport properties, which encompass the diffusion coefficients, electrical conductivities, viscosities and thermal conductivities, are computed. By comparing the values given by the simulations to reference experimental data, we show that this technique can now be considered as highly predictive"--